Singularity crossing phenomena in nonlinear electrical circuits - Kleiman, Diana Leonor (2017)
In a nonlinear system a singular crossing point is a singular point such that there is at least one solution crossing through it. In this article we study a family of nonlinear electrical circuits, that can be represented by nonlinear Implicit Differential Equations -IDEs-. We set conditions that ensure the existence of singular crossing points in these circuits. There are different approaches to this problem for a given general IDE, but the results we get for this family of circuits allow us to find these points in an extremely simple way. The results are illustrated in a concrete example.